Impact of Pharmacist–Psychiatrist Collaborative Patient Education on Medication Adherence and Quality of Life (QOL) of Bipolar Affective Disorder (BPAD) Patients - Mishra, Ambed; Krishna, Gudi S.; Alla, Sravani; Kurian, Tony D.; Kurian, Justin; Ramesh, Madhan; Kishor, M. (Frontiers in Pharmacology, 2017)
Background: Bipolar Affective Disorder (BPAD) is one of the leading causes of disability globally. Medication non-adherence and low quality of life (QOL) are the major challenges associated with the treatment of BPAD patients. Objective: Aim of this study was to assess the impact of pharmacist-psychiatrist collaborative patient education on medication adherence and QOL of BPAD patients. Methodology: A prospective randomized control study was conducted in the psychiatry outpatient department in a tertiary care setting. The eligible patients were enrolled and randomized into test (collaborative care) and control (usual care) groups. Patient education was provided by pharmacists to the test group patients, along with the usual care provided to all the patients. Patients were followed for three follow-ups of nearly one month intervals. Medication adherence and QOL were assessed by Medication Adherence Rating Scale and WHOQOL-BREF questionnaire respectively. T-test was used and P-values < 0.05 were considered statistically significant. Results: Out of 75 patients enrolled, 73 patients were followed for all the three follow-ups and completed the study. Thirty-eight patients belonged to test and 35 were in control group. The mean age of patients was 34.21 ± 10.91 years. Forty-eight (65.75%) patients belonged to age group of 18-39 years. There were 41 males (56.16%) and 32 female patients (43.83 %) in the study. Mean improvement in medication adherence and QOL of the test and control groups were found to be 2.06 ± 0.15 (< 0.001) and 13.8 ± 10.5 (<0.05) respectively. Conclusions: This study concluded that pharmacist-psychiatrist collaborative patient education can significantly improve the medication adherence and QOL of the BPAD patients. Statistically significant results indicating improved patient care and outcomes were possible when pharmacists worked as a team with psychiatrists.